ANALISIS PENERAPAN SUBJECT SPECIFIC PEDAGOGI (SSP) KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS DI SD 197/II PULAU PEKAN - Aldino (Jurnal Muara Pendidikan, 2025)
This research is motivated by an interest in curriculum change, which is a routine and common occurrence in countries with globally advanced education systems. Naturally, changes in the curriculum also affect the Subject Specific Pedagogy (SSP). Based on observations at SDN 197/II Pulau Pekan during IPAS (Science and Social Studies Integration) learning, it was found that some teachers understood the concept of SSP, while others, particularly novice teachers, were not yet familiar with it—likely due to the fact that they had not studied SSP during their university education. The implementation of the Merdeka Curriculum has already been carried out in all classes at SDN 197/II Pulau Pekan, from Grade I to Grade VI.This study employs a qualitative research approach, which involves procedures that generate descriptive data in the form of written or spoken words. The findings of the research indicate that in the implementation of Subject Specific Pedagogy in IPAS learning—as observed during the study at SDN 197/II Pulau Pekan—the researcher found several stages carried out by teachers in relation to the teaching module. These stages include: First, in the planning phase of IPAS learning in class VA, teachers at SDN 197/II Pulau Pekan are required to be creative in modifying the teaching modules provided by the Ministry of Education and Culture. Teachers must also be meticulous in selecting relevant topics and materials for IPAS instruction, considering both the available facilities and infrastructure, as well as the specific needs of the students.